Quantum Sensing of Local Magnetic Phase Transitions and Fluctuations near the Curie Temperature in Tm3Fe5O12 Using NV Centers - Yuqing Zhu; Mengyuan Cai; Qian Zhang; Peiyang Wang; Yuanjie Yang; Jiaxin Zhao; Wei Zhu; Guanzhong Wang (Micromachines, 2025)
Thulium iron garnet (Tm3Fe5O12, TmIG) is a promising material for next-generation spintronic and quantum technologies owing to its high Curie temperature and strong perpendicular magnetic anisotropy. However, conventional magnetometry techniques are limited by insufficient spatial resolution and sensitivity to probe local magnetic phase transitions and critical spin dynamics in thin films. In this study, we present the first quantitative investigation of local magnetic field fluctuations near the Curie temperature in TmIG thin films using nitrogen-vacancy (NV) center-based quantum sensing. By integrating optically detected magnetic resonance (ODMR) and NV spin relaxometry (T1 measurements) with macroscopic techniques such as SQUID magnetometry and Hall effect measurements, we systematically characterize both the static magnetization and dynamic spin fluctuations across the magnetic phase transition. Our results reveal a pronounced enhancement in NV spin relaxation rates near 360 K, providing direct evidence of critical spin fluctuations at the nanoscale. This work highlights the unique advantages of NV quantum sensors for investigating dynamic critical phenomena in complex magnetic systems and establishes a versatile, multimodal framework for studying local phase transition kinetics in high-temperature magnetic insulators.